FACTORS INFLUENCING UTILISATION OF PRE-EXPOSURE PROPHYLAXIS AGAINST HIV/AIDS AMONG FEMALE SEX WORKERS. A CASE STUDY OF KOOME ISLANDS MUKONO DISTRICT. A DESCRIPTIVE STUDY DESIGN. - NALUWOGO, JOHN JAMES; Kansiime, David (Student’s Journal of Health Research Africa, 2023)
Background: This study, therefore, sought to find out factors influencing the utilization of oral HIV Pre-Exposure prophylaxis among Female Sex Workers in Koome Islands. Methodology: Results were obtained using a convenience sampling technique. A target population of 124 respondents was included in the study. A researcher-based questionnaire was designed with relevant questions in line with the study objectives. Data were collected, entered, and analyzed critically using SPSS software. Results: PrEP use among FSWs was at 61.3%, and the level of self-perception as being at risk of contracting HIV infection among FSWs was at 96%. The majority of the FSWs were aware of HIV prevention with oral HIV PrEP. Conclusions: The study shows high self-perception as being at risk of contracting HIV infection among FSWs causing a high need for utilization of PrEP medicines. There is low utilization of PrEP among FSWs with lower levels of education despite their awareness of PrEP medicines. The findings from the study also show that a high proportion of FSWs would not afford PrEP medicines if they were not freely provided by the government and support organizations. The study findings show that the majority of FSWs did not access PrEP medicines because they were out of stock. Recommendations: The government should not only maintain the free provision of oral HIV PrEP medicines but also increase the amount of the medicines supplied to Koome Health Centre III to ensure easy access to and reduce shortages of PrEP medicines. The government should as well ensure a timely supply of PrEP medicines to Koome Health Center III. Healthcare providers should increase the counseling of FSWs before and after initiating them on PrEP medicines.